Pragmatic elements of the speech of Broca's aphasic patients: clinical preliminar study - Juliano Luis Fontanari (Arquivos de Neuro-Psiquiatria)
The author studies three patients with Broca aphasia characterized by the Boston Diagnostic Aphasia Examination, and following A.R. Luria's criterion on the use and comprehension of pragmatic elements of speech - deixis of time, person, place, discourse and social, implicatures of Grice, conventional, generalized and particularized and presupposition. For this, the author works on the development of three hours speech resulted from interviews and also uses specific tests. One of the patients lost the propositional content of speech and internal language, typical of severe dinamic aphasia. The other two showed instability in comprehension and use of time and place deixis only during the tests, not revealing this anomaly at non-artificial conditions. These findings suggest that metalanguage is upset with its specific temporo-spatial elements affected, and it is possible that there is a graduation in the loss of discourse linkage with verbal and nonverbal context in which mediation is made by pragmatic relation in frontal lesions.